Yoga Practice to Improve Woodball Gating Shoot in Woodball Athletes Sukabumi City - Nurudin, Ahmad Alwi; Wening Nugraheni; Dwi Tiga Putri (Jurnal Pendidikan Jasmani (JPJ), 2023)
The game of woodball requires athletes to concentrate fully on themselves and other objects that are internalized into the body, namely between hitting movements and other objects, namely the beater (malet) so that when the body reaches full attention or concentration, the accuracy of the strokes can hit the target properly. This study tries to reveal the effect of yoga on gating hitting in woodball athletes in Sukabumi City. The study used an experimental method with a one-group pretest-posttest research design. The population in this study were all Woodball athletes from Sukabumi, totaling 30 athletes.The instrument in this study was the gating skill test. The data analysis technique used in this study used t-test analysis using SPSS version 21. The results showed that there was an effect of yoga practice on the results of Woodball gating strokes in Woodball athletes from Sukabumi City. From the results of this study, yoga movements in general can have a positive effect on calmness and concentration when doing gating shots in woodball. The conclusion is that yoga exercises in increasing gating woodball strokes are yoga exercises that can help improve calm and concentration when hitting woodball.